Continuous-Flow Analysis of δ17O, δ18O, and δD of H2O on an Ice Core from the South Pole - Steig, Eric J.; Jones, Tyler R.; Schauer, Andrew J.; Kahle, Emma C.; Morris, Valerie A.; Vaughn, Bruce H.; Davidge, Lindsey; White, James W.C. (Frontiers in Earth Science, 2021)
The $δ$D and $δ^{18}$O values of water are key measurements in polar ice-core research, owing to their strong and well-understood relationship with local temperature. Deuterium excess, $d$, the deviation from the average linear relationship between $δ$D and $δ^{18}$O, is also commonly used to provide information about the oceanic moisture sources where polar precipitation originates. Measurements of $δ^{17}$O and ``$^{17}$O excess" ($Δ^{17}$O) are also of interest because of their potential to provide information complementary to d. Such measurements are challenging because of the greater precision required, particularly for $Δ^{17}$O. Here, high-precision measurements are reported for $δ^{17}$O, $δ^{18}$O, and $δ$D on a new ice core from the South Pole, using a continuous-flow measurement system coupled to two cavity ring-down laser spectroscopy (CRDS) instruments. Replicate measurements show that at 0.5 cm resolution, external precision is $\sim0.2 \permil$ for $δ^{17}$O and $δ^{18}$O, and $\sim1 \permil$ for $δ$D. For $Δ^{17}$O, achieving external precision of $\sim 0.01 \permil$ requires depth averages of $\sim$50 cm. The resulting $\sim$54,000 year record of the complete oxygen and hydrogen isotope ratios from the South Pole ice core is discussed. The time series of $Δ^{17}$O variations from the South Pole shows significant millennial-scale variability, and is correlated with the logarithmic formulation of deuterium excess ($d_{ln}$), but not the traditional linear formulation ($d$).